JOINT RESEARCH INTO DYNAMICS AND STRENGTH OF BANDSAW BLADES IN ROSENHEIM FACULTY OF WOOD TECHNOLOGY, GERMANY (Innovation in Woodworking Industry and Engineering design, 2026)
During DAAD 2013 research stay of the first author in Rosenheim Faculty of Wood Technology, joint research started into dynamics and strength of bandsaw blades. This paper is, in fact, the first one under the above title resulting from cooperation with Professor Scholz and his team. They have dealt with problems concerning dynamic instability of new sawblades with special crowned tooth shape. Studies had been carried out under various blade-tensioning and guide-system conditions. Now, FE analysis has been involved by means of Autodesk Inventor software. An approach has been proposed and developed for FE modelling the complicated buckling of bandsaw blades by substituting it with a sufficiently equivalent eccentric compression. Research results and conclusions on the reasons for the instability of blades with crowned tooth shape are presented.